1996
DOI: 10.1002/art.1780390404
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of TIMP‐1 production by oncostatin m in human articular cartilage

Abstract: Objective. To investigate the effects of the interleukind (IL-6) family cytokines, such as IL-6, IL-11, leukemia inhibitory factor (LIF), and oncostatin M (OSM), on the production of tissue inhibitor of matrix metalloproteinases 1 (TIMP-1) in human articular cartilage.Methods. Effects of IL-6 family cytokines and growth factors on TIMP-1 production were studied in human articular chondrocytes, grown as monolayer and cartilage explant culture. TIMP-1 protein levels in the cultured medium were measured by sandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…In extrapulmonary stromal cells, OSM stimulation in vitro induced the secretion of TIMP-1, a major inhibitor of MMP [42], suggesting that it might prevent ECM degradation. However, the effects of monocyte-derived OSM secretion on pulmonary stroma in a cytokine-rich milieu such as that of the tuberculous granuloma may be very different to data obtained in simple tissue-culture systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In extrapulmonary stromal cells, OSM stimulation in vitro induced the secretion of TIMP-1, a major inhibitor of MMP [42], suggesting that it might prevent ECM degradation. However, the effects of monocyte-derived OSM secretion on pulmonary stroma in a cytokine-rich milieu such as that of the tuberculous granuloma may be very different to data obtained in simple tissue-culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although p38 was constitutively phosphorylated in monocytes, inhibition of p38 signalling reduced OSM secretion, suggesting that this pathway is necessary although not sufficient for maximal Mtb-induced OSM secretion. Although JNK phosphorylation occurred in response to both Mtb and CoMTb, inhibition did not affect OSM secretion.In extrapulmonary stromal cells, OSM stimulation in vitro induced the secretion of TIMP-1, a major inhibitor of MMP [42], suggesting that it might prevent ECM degradation. However, the effects of monocyte-derived OSM secretion on pulmonary stroma in a cytokine-rich milieu such as that of the tuberculous granuloma may be very different to data obtained in simple tissue-culture systems.…”
mentioning
confidence: 99%
“…Activation of one of the two pathways may depend on the physiological condition or, alternatively, distinct pathways may be used in different FS cell subpopulations (80,99). A similar complexity is reflected in the expression of tissue-inhibitors of metalloproteinases (TIMPs) in pituitary cells: constitutive TIMP-II expression was observed in the FS cell line TtT/GF (83), whereas several of the cytokines produced by pituitary cells (IL-6, IL-10, LIF) -which are probably also produced within the FS cell compartment -were found to induce TIMP-I expression but not TIMP-II expression in various cell types including mononuclear phagocytes (100,101). The expression of TIMPs has generally been related to the preservation of extracellular matrix (ECM) components in various tissues (101).…”
Section: New Perspectives In Fs Cell Physiologymentioning
confidence: 99%
“…In addition, OSM has shown functions that are distinct from those of other members of the group. OSM stimulates tissue inhibitor of metalloproteinases 1 (TIMP-1) in synovial fibroblasts (25) and in human chondrocytes (26). We have recently shown that OSM can regulate the expression of IL-8, IL-6, and granulocyte-macrophage colonystimulating factor in cell culture (27) while other IL-6/ LIF cytokines do not.…”
mentioning
confidence: 99%